Central Corneal Thickness Increase Due to Stromal Thickening With Diabetic Peripheral Neuropathy Severity. Issue 9 (September 2018) - Kumar, Navasuja; Pop-Busui, Rodica; Musch, David C.; Reed, David M.; Momont, Anna C.; Hussain, Munira; Raval, Nilesh; Moroi, Sayoko E.; Shtein, Roni
Abstract : Purpose: To investigate the relationship between central corneal thickness (CCT) and diabetes disease severity among patients with diabetic peripheral neuropathy (DPN) compared with controls. Methods: In this cross-sectional study, 34 participants were examined. DPN status was assessed by clinical examination, nerve conduction studies, and quantitative sensory testing. All participants underwent comprehensive eye examination that included intraocular pressure measured by Goldmann applanation tonometry. CCT was measured by ultrasound pachymetry, and the thickness of corneal layers was assessed by corneal confocal microscopy. Association of CCT and DPN was examined using ANOVA. Results: Among the 34 participants, there were 9 controls, 16 patients with mild DPN, and 9 patients with severe DPN. CCT was significantly increased in the DPN groups compared with controls ( P = 0.0003). Mean CCT among controls was 552.7 ± 29.2 μm compared with 583.4 ± 25.0 μm in the mild DPN group and 613.3 ± 28.8 μm in the severe DPN group. In addition, stromal thickness differed significantly between the 3 study groups ( P = 0.045). Mean stromal thickness among controls was 439.5 ± 23.5 μm compared with 478.9 ± 37.5 μm in the mild DPN group and 494.5 ± 39.1 μm in the severe DPN group. Conclusions: This study demonstrates that CCT increases with DPN severity because of an increase in stromal thickness. CCT increase associated with DPN has important clinical implications including glaucoma progression, keratoconus susceptibility, and intraocular pressure assessment and should be accounted for when evaluating patients with diabetes.